Success Stories of Subanen Entrepreneurs: A Narrative Inquiry - Candia, Dain Kreser B.; Henteroliso, Felene Mabelle; Nacion, Ma Theresa S.; Ornopia, Bryle Christian V.; Batingal, Ace Virgel T.; Sumicad Jr., Eligen H. (Future Science / FSH-PH Publications, 2025)
This narrative inquiry investigates the success stories of Subanen entrepreneurs in Zamboanga del Sur, Philippines, addressing the research gap of limited localized studies on this specific indigenous group's entrepreneurial experiences. The study explores how cultural values, traditions, and socio-economic contexts influence their entrepreneurial success, highlighting the importance of cultural preservation alongside business innovation.